The Concept of Filling, Eliminating Gaps int Law and Ways to Overcome Them - Asatryan, Armen (Bulletin of Yerevan University C: Jurisprudence, 2023)
In the process of legal regulation of public relations, there are cases when individual public relations are not subject to legislative regulation, which may be due to legal gaps. The article considers the complete or partial absence of legal measures necessary to regulate public relations in the field of legal regulation.Moreover, due to the presence of gaps in Laws, problems arise in specifying the essence of the law and its implementation. The main means of filling the gap in the law is the publication of the missing norm, the need for which is dictated by life. If the law-making body failed to eliminate the gap, the procedure of parallel application of the law is applied. Parallelism refers to the similarity between certain tabular phenomena or objects.The application of judicial practice does not mean arbitrary decision of specific cases. Divination is accepted here in accordance with the principles of legality and justice.In jurisprudence , there are two main types of cohabitation: cohabitation by right and cohabitation by right. Based on what has been written, it can be noted that the opposition of the law is the solution of a specific legal case on the basis of such a legal norm, which is not intended for this, but for similar cases. If the competent authority resolves the case in accordance with the rulings on the norm governing such public relations, then in this case we are dealing with the opposition of the law. Judicial practice is the decision–making on a specific case based on the general principles and meaning of law. The opposition of law is applied when it is impossible to choose a similar rule of law in the absence of another. It should be noted that the combination of rights can be different. In this case, the legal case is considered (the case is regulated) on the basis of general principles and the meaning of law. This method is acceptable only if there is no similar rule of law in a given or homogeneous branch of law to regulate a particular phenomenon. At the same time, the fundamental, constitutional principles of law (equality before the law, justice, disclosure of truth, humanity and other principles) are put into effect.Analysis of the theory of gaps in law reveals significant terminological confusion in the use of the concepts of "remove", "fill", "overcome". In particular, V. Ya. Akimov notes that the courts have the necessary powers to fill in the gaps in the law. According to other authors (A. T. Bonner, E. S. Kemularia, V. V. Lazarev, A. S. Pigolkin, B. P. Spasov, V. N. Kartashov, etc.), only the law can really "fill" the existing legal gap. Within the framework of the domestic legal system, where "doctrine and legislation recognize as full-fledged sources of law only acts emanating from competent law-making bodies of state power and administration," only these bodies have the authority to fill in the gaps. All other state bodies "take an active part in identifying gaps, but are not entitled to eliminate them." Therefore, in the course of their activities, such bodies can only bridge the gap. One of the authors, A.T.Bonner, believes that the use of the term "filling" of legal gaps related to the activities of courts and their resolution of disputes by analogy is not correct, and based on what has been written, it can be noted that the use of the term "elimination" is not "filling" the gap" or "overcoming", allows them it is more adequate to reflect the essence of the actions carried out by regulatory authorities.Consequently, it can be concluded that the term "elimination of gaps" in the law reflects the essence of the activities of law-making bodies and the use of this term characterizes the activities of exclusively law-making bodies. As for the courts, these State bodies, in our opinion, fill the gap. In particular, no one disputes the fact that only a law-making body, not a law enforcement body, can finally eliminate a legal gap, and the court only temporarily fills it and for the most part applies only to one specific disputed case. For this reason, the main method of filling the gap in the law, analogy, is characterized as a one-time technique, relevant only for this case, "causal filling". The court, using well-known mechanisms for filling gaps (for example, the application of the law or the law by analogy), in some cases can only resolve a specific situation, but in no case create a precedent for making such a decision in the case. with similar circumstances.The article draws attention to the need to clarify the definition and use of the terms "elimination", "overcoming", "filling" legal gaps. In particular, the possibility of identifying the concepts of "eliminating the gap" and "filling the gap" should be completely excluded. In our opinion, in cases where it is not about eliminating gaps in general, but directly about the role of the judicial system in the process of filling these gaps, the term "filling the gaps" should be used. By "filling in the gaps" is meant the adoption by the competent state body (court) of a special decision on disputed legal relations, in the conditions of identifying a gap in legislation or law. The concept of "elimination of loopholes", implying their complete elimination in the system of law and law, should be recognized as the most adequate for the functions performed by the competent law-making bodies: legislative, executive, etc. The elimination of gaps is carried out through additions, while the addition is the prerogative of law-making bodies and represents the development of an insufficient rule of law.As for the term "bridging gaps", in our opinion, it has its own scope of application, it is the activity of competent state bodies (registration authorities, departmental committees, etc.), which often have to decide how it should be carried out in case of identification of gaps in legal regulation.Thus, the combination of the above concepts of "elimination", "filling", "overcoming" gaps in the unambiguous legal content of the law, as well as their concretization, in our opinion, will make it possible to more clearly identify the nature of the activities of legislative and law enforcement agencies in the process of filling and eliminating their gaps in law.
Keywords: Gap in law; law enforcement activity; legislation; non-regulation; analogy of law; law enforcement; court; perfection of law